Energy Dependence, Trade Balance, and Current Account Sustainability: Evidence From ASEAN-5 - Maulidar Agustina; M. Shabri Abd. Majid; Zia Thahira; Lidyana Dinda; Aulia Khairullah; Dwita Sakuntala (Heca Sentra Analitika, 2025)
This study investigates how energy dependence and trade structure influence current-account sustainability in the ASEAN-5 (Indonesia, Malaysia, Thailand, the Philippines, and Vietnam) over 2014–2023. Focusing on the region’s vulnerability to energy price volatility and evolving trade patterns, the analysis evaluates long- and short-run relationships between the current account, energy trade balance, overall trade balance, real GDP per capita, and exchange rate movements. A panel Autoregressive Distributed Lag (ARDL) model with a Pooled Mean Group (PMG) estimator is applied, and long-run robustness is verified using panel Fully Modified Ordinary Least Squares (FMOLS). The results confirm a stable long-run equilibrium in which both energy and non-energy trade balances significantly and positively contribute to current-account positions. Higher real income and a depreciated exchange rate are also associated with sustained current-account improvements, reflecting capacity expansion and expenditure-switching effects. Short-run adjustments differ across countries, shaped by their import dependence, energy mix, and external balance-sheet conditions. Robustness checks affirm the stability of the estimated long-run relationships. These findings highlight the importance of strengthening energy trade resilience, enhancing non-energy tradable sectors, and maintaining prudent exchange-rate flexibility to support external sustainability in the ASEAN-5.